Qadih Al-Farq among Fundamentalists & Polemicists - Azad, Ibtesam Muhammad (Journal of Islamic Sciences, 2022)
This is a short paper entitled ‘Qadih Al- Farq A Study Among Fundamentalists & Polemicists’. Due to the fact that Al- Farq is one of the means to be utilized in the process of Qiyas and to clarify the ways of Illah, it is highly recommended to be discussed in a separate paper, in fundamental and polemic point of view. The hypothetical inductive methodology has been followed here, that means going through the texts of fundamentalists and polemicists to summarize their opinions. The paper includes the topics like meaning of Al- Farq literally and idiomatically, opinions of the fundamentalists, then ends up with polemicists commentaries. The paper sums up that Qawadih, objections, questions – by all these Qiyas is objected, the fundamentalists who considered Al- Farq among the Qawadih, also had difference of opinions whether it is correct or not. In a nutshell – Al- Farq a considerable effective Qadih according the majority.